Characterization of Beta-Lactamases in Bloodstream-Infection Escherichia coli: Dissemination of blaADC–162 and blaCMY–2 Among Bacteria via an IncF Plasmid - Xiao, Linlin; Wang, Xiaotong; Kong, Nana; Zhang, Long; Cao, Mei; Sun, Muzhen; Wei, Quhao; Liu, Weiwei (Frontiers in Microbiology, 2019)
Objectives: To describe the molecular characteristics of beta-lactamases in bloodstream-infected Escherichia coli isolated from elderly patients, and to determine the genotypic patterns of blaCMY-2 and blaADC-162. Methods: A total of 50 bloodstream-infected E. coli isolates were obtained from patients aged >50 years at Shanghai Sixth People’s Hospital South Campus during 2015–2018. The isolates were subjected to beta-lactamase detection using phenotypic and molecular methods. Beta-lactamase genes were verified by sequencing and the phylogenetic relationships of the isolates were analyzed by multilocus sequence typing. The transferability of plasmids carrying blaCMY-2 and blaADC-162 genes was verified by conjugation experiments and plasmid replicon typing. Results: Eight beta-lactamase subtypes were detected in 50 isolates of bloodstream-infected E. coli. blaTEM-1 (21/50) was the most common beta-lactamase gene, followed by blaCTX-M-14 (8/50), blaOXA-27 (5/50), blaCTX-M-27 (3/50), blaCTX-M-65 (1/50), blaADC-162 (1/50), and blaCMY-2 (1/50). Of these, blaADC-162 (ST95-A), and blaCMY-2 (ST95-B2) have not previously been reported in bloodstream-infected E. coli. In 21 isolates, beta-lactamase genes were located on conjugative plasmids belonging to incompatibility groups FrepB (n=7), FIA (n=1), FIC (n=2), K (n=8), N (n=1), and I (n=1), and blaCTX-M was associated with the common elements ISEcp1, IS903, and IS26, but with special sequences (region V, region Y, and region W) for ISEcp1 in 14 isolates. Conclusions: To the best of our knowledge, this study provides the first molecular characterization of beta-lactamase genes in E. coli isolated from the bloodstream in elderly patients. Beta-lactamase genes were detected at a relatively high frequency in elderly patients with bloodstream E. coli infections. Plasmid replicon analysis showed that horizontal dissemination of beta-lactamase genes was mainly mediated by IncK and IncF plasmids, which could encode multidrug resistance genes. The study also provides the first report of ISAba1-blaADC-162-tnpA and ISEcp1-blaCTX-M-14-IS903-blaCMY-2-blc-sugE in E. coli, and demonstrates IncF plasmid-mediated blaADC-162 and blaCMY-2 gene dissemination among bacteria.